Design and performance analysis of energy efficiency based CR primary user emulation attack defensive scheme - Yunchuan WANG; Xiaorong XU; Yingbiao YAO; Weiwei WU (Dianxin kexue)
Energy efficiency based PUEA defensive scheme was investigated with performance analysis.In this scheme,CSS energy efficiency was constructed as the optimum objective in the presence of PUEA with secure detection probability and false alarm probability threshold as the constraint conditions.Secure CSS model and PUEA defensive scheme were proposed to achieve energy efficiency based secure CSS.K-out-of-N criterion is set as global decision criterion in the scheme.Optimal fusion threshold K and optimal cooperative SUs N can be determined in secure CSS with the guarantee of energy efficiency.Compared with the traditional maximum ratio combining (MRC) fusion rule,the proposed PUEA defensive scheme not only guarantees system energy efficiency,but also improves system detection performance.Namely,the proposed scheme makes a trade-off between energy efficiency and detection performance in the presence of PUEA.The numerical simulation results show that the proposed strategy is not affected by the PUE interference power,and it has a high degree of persistence for PUEA attack.